2019
DOI: 10.1111/eth.12976
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of mate choice for red carotenoid coloration in the marine copepod Tigriopus californicus

Abstract: Colorful ornaments are hypothesized to have evolved in response to sexual selection for honest signals of individual quality that provide information about potential mates. Red carotenoid coloration is common in diverse groups, and in some vertebrate taxa, red coloration is a sexually selected trait whereby mates with the reddest ornaments are preferred. Despite being widespread among invertebrates, whether red carotenoid coloration is assessed during mate choice in these taxa is unclear.The marine copepod Tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…It could be that the malnourishing yeast diet limited variation in offspring development, slowing all lines and changing the relationship between offspring development and astaxanthin bioconversion. These results could support the idea that astaxanthin pigmentation is fundamentally tied to individual condition [ 2 , 24 ], even in systems that do not experience sexual selection on carotenoid coloration [ 49 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It could be that the malnourishing yeast diet limited variation in offspring development, slowing all lines and changing the relationship between offspring development and astaxanthin bioconversion. These results could support the idea that astaxanthin pigmentation is fundamentally tied to individual condition [ 2 , 24 ], even in systems that do not experience sexual selection on carotenoid coloration [ 49 ].…”
Section: Discussionsupporting
confidence: 62%
“…Prior to the start of the experiment, RIL copepods were switched to a diet of ground nutritional yeast until they became clear in color and deficient of both carotenoid precursors and the primary red carotenoid, astaxanthin [ 9 , 49 ]. To test carotenoid bioconversion rate, carotenoid-deficient copepods were provided Tetraselmis chuii algae ad libitum for 7 days to mimic the copepod’s natural diet of photosynthetic algae rich with carotenoid precursors [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the yeast-only inbred lines, we found that offspring from all lines developed at similar rates (S3 Fig); however, in the reciprocal cross between SD and SCN fed algae, we found that development rate was significantly longer in hybrids by the third generation (S14C Fig) . We have frequently observed longer development rates in laboratory cultures fed yeast-only diets, and in the data in this study we also observed that parental copepods fed yeast only produced offspring with longer development rates on average compared to parental copepods fed algae (S1E Fig) . It could be that the malnourishing yeast diet limited variation in offspring development, slowing all lines and changing the relationship between offspring development and astaxanthin bioconversion. These results could support the idea that astaxanthin pigmentation is fundamentally tied to individual condition [2,24], even in systems that do not experience sexual selection on carotenoid coloration [49].…”
Section: Plos Onesupporting
confidence: 66%
“…We hypothesize that copepods combine both astaxanthin and structures in a similar manner to jumping spiders, which is why their eyespots appear non-iridescent under light microscopy. Jumping spiders and other bright red animals like house finches ( Haemorhous mexicanus ) produce red colour for display, but the red eyespot of a copepod is unlikely involved in sexual signalling [21,46,47]. Instead, the bright red eyespot colour, that is present in many other organisms as well, may have a functional role.…”
Section: Discussionmentioning
confidence: 99%